Expanding the logistics business into China - Chaweewan Gatepithaya (2013)
China’s economy has been growing strongly which currently holds the 2nd largest GDP in the world. The economic growth in China started from the coastal areas 30 years ago. Recently, with aim of expansion of domestic demand, China has shifted its focus to the economic development of inland areas where they have huge domestic market. However, since China has been focused strongly on other industry sectors, its logistics industry, which plays a key role for its further economic growth, remains rudimentary and inefficient. Thus, China has been investing for setting up several logistics centers in inland area and starting to provide favorable conditions for foreign investors.